Practical widow to passionate mistress eaudiobook Transformation of the shelley sisters series, book 1. - Allen, Louise (Transformation of the Shelley Sisters, 2012)
Louise Allen's sumptuous prose has won the author a fervent following for her historical romances. A young widow in search of a new life, Meg happens upon the unconscious Major Brandon on the Bordeaux docks. Posing as his wife, she helps him aboard a ship for England. With some convincing, the major agrees to take her on as his housekeeper-and possibly much more. "Allen reaches into readers' hearts."-Romantic Times